Occupational anxiety and self-efficacy levels among prospective teachers - Şule Fırat Durdukoca; Tazegül Demir Atalay (International Journal of Evaluation and Research in Education (IJERE), 2019)
This study examined the relationship between occupational anxiety and self-efficacy levels of prospective teachers enrolled in pedagogical formation training certificate program at the faculty of education in universities under the Council of Higher Education to teach in secondary schools and high schools in Turkey, and evaluated them based on diverse variables (gender, department, high school type, educational level of parents). It was a descriptive study using survey model. The study group comprised 236 prospective teachers. Research data were gathered through “Teaching Occupation Anxiety Scale” and “Teachers’ Sense of Efficacy Scale”. The study concluded that the prospective teachers’ anxiety about the teaching profession was low, whereas they had high occupational self-efficacy, and there was a moderate, negative relationship between the two variables. The study also found that occupational self-efficacy levels of the participants differed in relation to the educational level of father.